Collaborative usage of ICT DBMS in construction cost control: requirements for development and users perception - Bandi, Shamsul Hadi (2008)
The development of construction industry in recent years has witnessed tremendous amount of information and data being produce throughout the construction stage. Better management of information and data are therefore required to facilitate such a progress and preparation with ICT becoming the focus of development. This paper aims on developing an iDBMS as a tool to facilitate data/information sharing and retrieval by utilizing Microsoft.Net framework. In order to proceed with the study, user requirements study has been conducted to solicit user needs before iDBMS being develop. It was later followed by iDBMS trial run, where data collected from questionnaire survey conducted during iDBMS trial run is analyzed by using Average Index Analysis (A.I.A) with corresponding evaluation table provided for reference. Finally, this study will conclude by outlining in details about all feedback gathered and recommendations which are important in order to sustain the presence of ICT DBMS particularly in the construction industry.